Gardner Intelligence in Physics Students in Maluku, Indonesia - John Rafafy Batlolona; Arman Kalean (Postgraduate, University of Mataram, 2023)
In this study investigated Gardner's intelligence in physics students. The sample surveyed was 360 physics students, namely physics education study programs, physics and elementary school teacher education at several universities in Maluku. The instrument used is Gardner's 1999 intelligence with 24 questions out of 9 intelligences. The results obtained indicate that the intelligences that are superior to ethnic physics students in Maluku are Mathematical Logic, Music, Interpersonal and Naturalistic. While verbal, kinesthetic, intrapersonal, and spatial intelligence is still weak. Therefore, it is necessary to apply models, strategies, and approaches and techniques that are appropriate in increasing student intelligence. To increase Gardner science student intelligence, at least pay attention to Gardner intelligence (GI) theory in the science curriculum. These findings may help to provide some practical implications for the development of effective problem-solving, creativity, critical and communicative skills in teaching physics